2020
DOI: 10.3389/fpsyg.2020.588648
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Value Co-creation Literature in the Technology and Innovation Management Field: A Bibliographic Coupling Analysis

Abstract: Value co-creation has become a very important topic in several disciplines. It is observed that value co-creation has been analyzed mainly from a perspective of marketing or services. The interest of studying value co-creation in relation to innovation is growing but there are no previous literature reviews that focus on the literature that studies value co-creation from a technology and innovation management perspective. The present research aims to close this gap. This research has two aims. First, we make a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 142 publications
(255 reference statements)
1
12
0
3
Order By: Relevance
“…There is a research vacuum (void) between open science, Innovation and co-creation (Ramirez & Penalvo, 2018;Najera-Sanchez et al, 2020). Huizingh (2011) argues that the context of open innovation is poorly understood, requiring research on the organizational characteristics of co-creation of the internal and external environment (Prahalad & Ramaswamy, 2004b).…”
Section: Introductionmentioning
confidence: 99%
“…There is a research vacuum (void) between open science, Innovation and co-creation (Ramirez & Penalvo, 2018;Najera-Sanchez et al, 2020). Huizingh (2011) argues that the context of open innovation is poorly understood, requiring research on the organizational characteristics of co-creation of the internal and external environment (Prahalad & Ramaswamy, 2004b).…”
Section: Introductionmentioning
confidence: 99%
“…Nájera-Sanchez et al. (2020) made a bibliographic coupling analysis on co-creation and extended it to many stakeholders, pointing that the client can play several roles such as being a source of information, co-developer and innovator.…”
Section: Value Co-creationmentioning
confidence: 99%
“…In terms of driving factors, Baines et al (2020) investigated the process of organizational change generated by servitization to analyze the drivers of servitization. Nájera-Sánchez et al (2020) identified value co-creation as an important driving factor for firms to develop servitization via a bibliographic coupling analysis. In terms of future research directions, Khanra et al (2021) recommended actionable future research agendas on servitization by systematically analyzing the servitization literature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the Industry 4.0 era, the servitization of manufacturing is a new business model and production pattern ( Weking et al, 2020 ). In this context, more manufacturers are considering its servitization with a strategic change from manufacturing products simply to providing product service ( Nájera-Sánchez et al, 2020 ; Liu et al, 2022 ). Because the homogenization of tangible products is an inevitable trend, it is only to create a competitive advantage of differentiation among them through service innovation ( Baines et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%